Strategic NPV - Smit, Han T. J.; Trigeorgis, Lenos (Strategic Management Journal, 2017)
[Research summary: Among themost difficult firm strategic choices is the trade-off between making a long-term commitment or holding off on investment in the face of uncertainty. To operationalize strategic management theory under demand, technological and competitive uncertainty, we develop a Strategic Net Present Value (NPV) framework that integrates real options and game theory to quantify value components and interactions at the interface between NPV, real options, and strategic games. Our approach results in new propositions clarifying the way learning-experience conditions, technological uncertainty, and proprietary information interact to tilt the balance in the interplay between wait-and-see flexibility and strategic commitment. As such, Strategic NPV adds to our understanding of the conditions where NPV, real options, or strategic thinking are more relevant. Managerial summary:This study develops and elucidates implementation of a new valuation construct, “Strategic Net Present Value (NPV),” that integrates real options and game theory to more accurately portray strategic decisions underlying management theory. Among the most difficult firm strategic choices in capital intensive industries, such as energy, mining, chip manufacturing, and infrastructure development, is the trade-off between making a long-term commitment or holding off on investment in the face of demand, technological, and competitive uncertainties. The study provides new insights on the way various conditions, such as learning-experience effects, technological uncertainty, and proprietary information, interact to tilt the balance in the interplay between commitment and wait-and-see flexibility. As such, Strategic NPV adds to our understanding of when NPV, real options, or strategic thinking matter more critically for decision making.]